'Let's Cut Queues and Play the Game': The Origin and Evolution of Chinese Involvement in American Baseball, 1870–1935. Issue 12 (13th August 2017) - Yu, Xiaowei
Abstract: In the early period of its development in America, baseball not only helped immigrants from all over the world become assimilated into the culture of a new country, in effect, the diamond sport also became a cultural export to other countries. Though numerous historical studies have focused on early baseball players from various ethnic groups in America, there have been few examinations focusing on the early development of baseball among Chinese immigrant communities. Some questions are appropriate. In the nineteenth century, what role, if any, did the Chinese play in the presence of baseball in both China and the United States? Similar to other ethnic baseball aggregations in America, were there such entities as 'all-Chinese' baseball teams? Were there Chinese baseball players who became famous among Chinese communities scattered throughout the country? To respond to these questions, the examination is organized into three dimensions: the early development of baseball in China; the early baseball experience of both young students from China and Chinese people residing in mainland America; and the American tours of the Chinese–Hawaiian team of pre- and post-First World War.